Cartographie De La Dynamique Du Trait De Cote A Grand-Lahou : Utilisation De L’outil « Digital Shoreline Analysis System (Dsas)» - M. Valère, Djagoua Eric; Fatoumata, Bakayoko; Jeanne, Kouadio Maffoué; Jean-Baptiste, Kassi A.; Brice Hervé, Mobio A.; Kouamé, Adonis Krou; André, Tiemélé Jacques; Patricia, Yavo (European Scientific Journal, ESJ, 2016)
Like many coasts, coastal erosion is evident on all the Ivorian coast and is characterized by the destruction of physical assets (infrastructure, habitat and sightseeing). Especially in Grand-Lahou, it threatens a fishing village located on a strip of land 200 meters separating the Atlantic Ocean from the Tadjo lagoon and facing the mouth of the Bandama River. To contribute to the choice of sustainable coastal development in Grand-Lahou, this study aims to characterize the dynamics of the coastline by performing coastal erosion map locally for the best appreciation of the erosion phenomenon. To do this, the GIS which consisted of compilation of coastlines data from Landsat images from 1998, 2001, 2005, 2009, 2011 and 2014 in the study area. The dynamic of the coastline in this zone was done through the Digital Shoreline Analysis System (DSAW). The variations observed between 1998 and 2014 show a coastline fattening at an average rate of 2.09 m / year in the west of the river mouth before Lahou-Kpanda village and erosion with a speed of 0.84 m / year on rest of the shore after Lahou Kpanda village.